2013
DOI: 10.1007/s12199-013-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking with intraocular pressure in middle-aged and older Japanese residents

Abstract: Objectives To clarify whether smoking was associated with elevated intraocular pressure (IOP) and to evaluate the interrelationship among IOP, blood viscosity, and smoking. Methods This cross-sectional study analyzed health examination data obtained between 2001 and 2004 from 1113 individuals (829 men and 284 women), ranging in age from 28 to 79 years, who had not undergone any ocular surgery or medical treatment for hypertension, ocular hypertension, and glaucoma. Results Multiple-regression analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
(10 reference statements)
4
17
2
Order By: Relevance
“…Previous studies showed that the changes in BMI, 5,15,17,20,27,[29][30][31] SBP, 18,27,32,33 DBP, 33 and HbA1c 18,26,34,35 were positively correlated with the change in IOP. In the present study of Japanese individuals, the age-related reduction in IOP was significantly greater in males than in females, which is consistent with the findings of previous reports.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies showed that the changes in BMI, 5,15,17,20,27,[29][30][31] SBP, 18,27,32,33 DBP, 33 and HbA1c 18,26,34,35 were positively correlated with the change in IOP. In the present study of Japanese individuals, the age-related reduction in IOP was significantly greater in males than in females, which is consistent with the findings of previous reports.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study of Japanese individuals, the age-related reduction in IOP was significantly greater in males than in females, which is consistent with the findings of previous reports. 5,15,17,18,20,26,27,29,[31][32][33][34][35] The majority of previous papers have reported positive correlations between obesity and IOP. However, there was evidence for interference and multicollinearity among the factors; consequently, 8 factors were selected based on the results of univariate regression analysis, and were included in multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are in contrast with findings of earlier studies 27,28 , which reported reduced pRNFLT in smokers. Suggested mechanisms leading to decreased pRNFLT were toxic damage through free radicals, increased IOP and reduced perfusion [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…A smaller proportion of obese and hypertensive subjects exist in the elderly groups due to the increased mortality of cardiovascular disease, and therefore IOP would seem to be lower with age in the absence of these risk factors, forming the rear decline of this curve. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%